An under‐recognized phenomenon: Myocardial volume change during the cardiac cycle. Issue 8 (4th June 2021) - Kumar, Vinayak; Manduca, Armando; Rao, Chaitanya; Ryu, Alexander J.; Gibbons, Raymond J.; Gersh, Bernard J.; Chandrasekaran, Krishnaswamy; Asirvatham, Samuel J.; Araoz, Philip A.; Oh, Jae K.; Egbe, Alexander C.; Behfar, Atta; et al.
Abstract: Background: Myocardial volume is assumed to be constant over the cardiac cycle in the echocardiographic models used by professional guidelines, despite evidence that suggests otherwise. The aim of this paper is to use literature‐derived myocardial strain values from healthy patients to determine if myocardial volume changes during the cardiac cycle. Methods: A systematic review for studies with longitudinal, radial, and circumferential strain from echocardiography in healthy volunteers ultimately yielded 16 studies, corresponding to 2917 patients. Myocardial volume in systole (MVs) and diastole (MVd) was used to calculate MVs/MVd for each study by applying this published strain data to three models: the standard ellipsoid geometric model, a thin‐apex geometric model, and a strain‐volume ratio. Results: MVs/MVd<1 in 14 of the 16 studies, when computed using these three models. A sensitivity analysis of the two geometric models was performed by varying the dimensions of the ellipsoid and calculating MVs/MVd. This demonstrated little variability in MVs/MVd, suggesting that strain values were the primary determinant of MVs/MVd rather than the geometric model used. Another sensitivity analysis using the 97.5th percentile of each orthogonal strain demonstrated that even with extreme values, in the largest two studies of healthy populations, the calculated MVs/MVd was <1. Conclusions: Healthy human myocardium appears to decrease in volume during systole. This is seen in MRI studies and is clinically relevant, but this study demonstrates that this characteristic was also present but unrecognized in the existing echocardiography literature.